Evaluating the Capability of the Flux-Limiter Schemes in Capturing Strong Shocks and Discontinuities - Iman Harimi; Ahmad Reza Pishevar (Shock and Vibration)
A numerical study is conducted to investigate the capability of the flux-limiter TVD schemes in capturing sharp discontinuities like shock waves. For this purpose, four classical test problems are considered such as slowly moving shock, gas Riemann problem with high density and pressure ratios, shock wave interaction with a density disturbance and shock-acoustic interaction. The governing equations consist of one-dimensional and quasi-one-dimensional Euler equations solved using an in-house numerical code. In order to validate the solution, the obtained results are compared with other results found in the literature.